Tinjauan Permainan Kesenian Irama Minang (KIM) Sebagai Budaya Masyarakat Minangkabau - Dwi Catur Berlianda; Yudi Sukmayadi (SENDRATASIK UNP, 2024)
Every region certainly has games that are often used on certain occasions andcan even be said to be part of their culture. The purpose of this study is to review one of the games in West Sumatera namely Kesenian Irama Minang (KIM) game so that it has become one of the popular cultural games in Minangkabau. In this research, the approach used is a qualitative approach with descriptive analysis methods and the data was collected by means of interviews and literature studies to complete statements from the interview results.The results found that the KIM game was introduced in the Pariaman area of West Sumatra and was first popularized at weddings. Looking at the popularity of the KIM game researchers reviewed it from a musical perspective and concluded that the KIM game has different song forms, the poems are like rhymes with rhymes a-ba-b using the Minang regional language and use a fast tempo or what is usually called with Allegro.